How to improve donor skin availability: Pragmatic procedures to minimize the discard rate of cryopreserved allografts in skin banking. Issue 2 (March 2021) - Germain, Nicolas; Hatzfeld, Anne-Sophie; Pasquesoone, Louise; Danze, Pierre- Marie; Guerreschi, Pierre; Sendid, Boualem; Gaillot, Olivier; Marchetti, Philippe
Highlights: Long-term incubation of skin into the antibiotic cocktail is crucial to reducing the rate of contaminated allograft. Splitting the procurement into several anatomical zones from each skin donor reduces the risk of cross-infection. Allografts contaminated with low bioburden of saprophytic and non-pathogenic germs can be accepted for safe clinical use. Abstract: Background: Microbial contamination of human skin allografts is a frequent cause of allograft discard. Our purpose was to evaluate the discard rate of skin bank contaminated allografts and specific procedures used to reduce allograft contamination without affecting safety. Methods: We conducted at the Lille Tissue Bank a retrospective study of all deceased donors (n = 104) harvested from January 2018 to December 2018. Skin procurement was split into 3 zones: the back of the body and the two legs that were processed separately. It represented 433 cryopreserved skin allograft pouches of approximatively 500 cm² each. Donors were almost equally split between brain-dead (53%, 55/104) and cadaveric (47%, 49/104) donors. Results: Out of all donors, 42 (40.5%) had at least one sampling zone with a positive microbiological test resulting in 106 (24%) contaminated skin pouches. The contamination rate did not vary according to the harvested zone or type of donor. Traumatic deaths showed significantly less contamination rates than other death types (p < 0.05). Contamination rate decreased with time spent in the antibiotic solution. The risk of having contaminated allografts was five-fold higher when the skin spent less than 96 h in the antibiotic cocktail (p < 0.05). According to our validation protocol, most donors (32/42, 76%) had skin allografts contaminated with bacteria (mainly Staphylococcus spp ) compatible with clinical use. No recipient infection was recorded as a result of skin graft contaminated with saprophytic or non-pathogenic germs. By harvesting 3 separate zones per donor, the total surface area for clinical use increased by 53% for contaminated donors. Overall, the proportion of contamination-related discarded allografts was 3.2% (14/433 of pouches). Conclusion: Few simple pragmatic measures (including skin incubation in the antibiotic bath for at least 96 h at 4 °C, splitting the skin harvesting areas to minimize the risk of cross-infection and clinical use of allografts contaminated with saprophytic and non-pathogenic germs) can reduce the discard rate of contaminated allografts without affecting clinical safety.